Piezoelectric response to coherent longitudinal and transverse acoustic phonons in a semiconductor Schottky diode - Srikanthreddy, D.; Glavin, B.A.; Poyser, Caroline Louise; Henini, M.; Lehmann, D.; Jasiukiewicz, Cz.; Akimov, Andrey V.; Kent, A.J. (American Physical Society, 2017)
We study the generation of microwave electronic signals by pumping a (311) GaAs Schottky diode with compressive and shear acoustic phonons, generated by femtosecond optical excitation of an Al _lm transducer and mode conversion at the Al-GaAs interface. They propagate through the substrate and arrive at the Schottky device on the opposite surface, where they induce a microwave electronic signal. The arrival time, amplitude and polarity of the signals depend on the phonon mode. A theoretical analysis is made of the polarity of the experimental signals. This includes the piezoelectric and deformation potential mechanisms of electron-phonon interaction in a Schottky contact and shows that the piezoelectric mechanism is dominant for both transverse and longitudinal modes with frequencies below 250 GHz and 70 GHz respectively.